Kyphoplasty in patients with multiple myeloma a retrospective comparative pilot study - Kasperk, Christian; Haas, Andreas; Hillengaß, Jens; Weiß, Christel; Neben, Kai; Goldschmidt, Hartmut; Sommer, Ulrike; Nawroth, Peter Paul; Meeder, Peter-Jürgen; Wiedenhöfer, Bernd; Schmidmaier, Gerhard; Tanner, Michael Christopher; et al. (Journal of surgical oncology, 2012)
Background This retrospective study of 73 myeloma patients with painful vertebral lesions compares clinical and radiomorphological outcomes up to 2 years after additional kyphoplasty, radiation therapy or systemic treatment only. Methods We assessed pain, disability and radiomorphological parameters by visual analogue scale (VAS 0-100), Oswestry Disability Index and by re-evaluating available follow-up X-rays, respectively, in patients that were treated according to a clinical pathway. Results After 2 years the VAS score was reduced in all groups by 66 ± 8.2 (kyphoplasty), 35 ± 10.5 (radiation therapy) and 38 ± 20.5 (systemic therapy only). Only after kyphoplasty we observed a significantly reduced Oswestry Disability Index after 1 year (P < 0.001). Vertebral height remained stable after kyphoplasty (P = 0.283), in contrast to a progressive height loss in the other groups (P = 0.013 and P = 0.015 for radiation and systemic therapy only, respectively). Two years after kyphoplasty and radiotherapy the overall vertebral fracture incidence was significantly decreased as compared to the group after systemic therapy only (9.7% of all thoracic and lumbar vertebrae had new vertebral fractures after systemic therapy only, 2% after kyphoplasty (P < 0.001), 4.8% after radiation (P = 0.032)). Conclusion Additional kyphoplasty was more effective than additional radiation or systemic therapy in terms of pain relief, reduction of pain associated disability and reduction of fracture incidence of the entire lumbar and thoracic spine. J. Surg. Oncol. 2012; 105:679-686. © 2011 Wiley Periodicals, Inc.